The Nollywood cultural effect in Zimbabwe: manifestation of Nigerian lingo in everyday discourses - Mpofu, Phillip (Routledge, 2022)
The Nollywood films, Nigeria’s greatest cultural export, have had phenomenal cultural impact in Zimbabwe. Deploying a theoretical gaze grounded in the social learning theory and notions of linguistic diffusion, lexical and pragmatic borrowing, this article explores the manifestation of lexis, accents, semantic and pragmatic elements of Nigerian linguistic and cultural heritage in Zimbabwe’s everyday discourses, as well as cultural productions. The corpus of Nigerian lingo was developed using a combination of qualitative methods that included personal interviews, focus groups and observation methods. The diffusion and use of Nigerian lingo in Zimbabwe proves films’ expediency in extemporaneous foreign language learning. The language acquisition process is induced by the cultural appeal of Nollywood films and the idolisation of people and culture depicted in the films. The adoption and adaptation of Nigerian lingo in Zimbabwe as a result of exposure to Nollywood movies is a significant contribution to discourses of multiculturalism.